Contraceptive Provision to Postpartum Women With Intellectual and Developmental Disabilities: A Population‐Based Cohort Study. Issue 3 (29th May 2018) - Brown, Hilary K.; Kirkham, Yolanda A.; Lunsky, Yona; Cobigo, Virginie; Vigod, Simone N.
Abstract : CONTEXT: Women with intellectual and developmental disabilities who experience pregnancy, like all women, require postpartum care that supports their contraceptive knowledge and decision making. Yet, little is known about the postpartum contraceptive care these women receive, or how it compares with care given to other women. METHODS: A population‐based study using linked health and social services administrative data examined provision of postpartum contraceptive care to women who had a live birth in Ontario, Canada, in 2002–2014 and were beneficiaries of Ontario's publicly funded drug plan. Modified Poisson regression was used to compare care between 1, 181 women with and 36, 259 women without intellectual and developmental disabilities. Outcomes were provision of any nonbarrier contraceptive in the year following the birth and type of method provided. RESULTS: In the first year postpartum, women with intellectual and developmental disabilities were provided with contraceptives at a higher rate than were other women (relative risk 1.3); the difference was significant for both nonsurgical and surgical methods (1.2 and 1.8, respectively). The higher rate of nonsurgical contraceptive provision was explained by provision of injectables (1.9); there were no differences for pills or IUDs. CONCLUSION: Nonbarrier contraceptives may be the most appropriate methods for some women with intellectual and developmental disabilities. However, future research should investigate why women with such disabilities are more likely than others to receive injectable contraceptives, which have possible negative side effects, and surgical contraception, which is irreversible. Research also should investigate how these women perceive their participation in contraceptive decision making.